Electrical characterization and equivalent circuit analysis of (Bi1.5Zn0.5)(Nb0.5Ti1.5)O7 Pyrochlore, a relaxor ceramic - Rozana Aina, Maulat Osman, Dr.; West, Anthony R. (The American Institute of Physics (AIP), 2012)
Link to publisher's homepage at http://www.aip.org/